Dare, dream, do remarkable things happen when you dare to dream - Johnson, Whitney (Bibliomotion, 2012)
"Johnson directs her attention to teaching us a three-step model for personal advancement and happiness. She first encourages us to DARE to boldly step out, to consider disrupting life as we know it. She then teaches us how to DREAM, to give life to the possibilities, whether to start a business or run a marathon. Finally, Johnson's model brings out the businesswomen in her; she teaches us to DO, to execute our dreams, partly by showcasing the importance of sharing our dreams with others."--Provided by publisher